RESPON PERTUMBUHAN DAN HASIL KACANG HIJAU (Vigna radiata L.) TERHADAP BERBAGAI DOSIS PUPUK NITROGEN DAN JARAK TANAM - Yudianto, Feri (Universitas Islam Balitar, 2016)
This research intent 1) To know influence of type interaction manures nitrogen with distance plants out to growth and green bean plant result, 2 ) To know difference influence manure nitrogens to growth and green bean results, 3 ) To know distance purpose influences plant out to growth and green bean results. This research is done by use of agglomerate Random Design one was arranged by ala Factorial (RACK) with 2 factors, first factor which is nitrogenic manure dose urea (N ) one consist 3 levels which is N1 (N 100 kg / ha), N2 (N 150 kg / ha) and N3 (N 200 kg / ha). Second factor which is implant distance (J. ) one consists 2 levels which is J1 (30x20) and J2 (30x30). Observed parameter high cover plant, total productive branch, wight grades about plant upon harvests. dianalisis's data by use of analisis manner (Anova), if ascendant drawned out by DMRT'S quiz 5%. Result observationaling to point out that: 1 ). Dosed application manures urea's nitrogen 200 kg / ha give influence besting to growth and green bean plant results. 2 ). Distance plants out not give influence besting to growth and green bean plant result, but upon crop gives influence besting to growth and green bean plant result.